Interface propagation and energy dissipation in Shape Memory Alloys. (June 2023) - He, Y.J.
Abstract: Recent experiments showed that the macroscopic interface propagation of the martensitic phase transformation in Shape Memory Alloys (SMAs) includes unstable microstructure evolution in the macroscopic diffuse interfacial zone (with nucleation, branching, merging and/or annihilation of numerous small domains), releasing the stored energy of the diffuse interface. In this paper, with a one-dimensional Cahn-Hilliard model, a quantitative relation between the energy dissipation and the interfacial properties (interface energy and interface thickness) is revealed: the energy dissipation is governed by the energy barrier caused by the diffuse interface. The relation is verifiable with existing experiments. It can also help understand the interfacial effect on the material's fatigue failure and provide a hint to search for low-hysteresis SMAs: weak first-order phase transformation implies weak energy dissipation (low hysteresis). Graphical abstract: Image, graphical abstract